Predicting Ca2+ and Mg2+ ligand binding sites by deep neural network algorithm - Sun, Kai; Hu, Xiuzhen; Feng, Zhenxing; Wang, Hongbin; Lv, Haotian; Wang, Ziyang; Zhang, Gaimei; Xu, Shuang; You, Xiaoxiao (BMC bioinformatics, 2022)
Background Alkaline earth metal ions are important protein binding ligands in human body, and it is of great significance to predict their binding residues. Results In this paper, Mg 2+ and Ca 2+ ligands are taken as the research objects. Based on the characteristic parameters of protein sequences, amino acids, physicochemical characteristics of amino acids and predicted structural information, deep neural network algorithm is used to predict the binding sites of proteins. By optimizing the hyper-parameters of the deep learning algorithm, the prediction results by the fivefold cross-validation are better than those of the Ionseq method. In addition, to further verify the performance of the proposed model, the undersampling data processing method is adopted, and the prediction results on independent test are better than those obtained by the support vector machine algorithm. Conclusions An efficient method for predicting Mg 2+ and Ca 2+ ligand binding sites was presented.